If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -28 = 6(v + -6) + -8v Reorder the terms: -28 = 6(-6 + v) + -8v -28 = (-6 * 6 + v * 6) + -8v -28 = (-36 + 6v) + -8v Combine like terms: 6v + -8v = -2v -28 = -36 + -2v Solving -28 = -36 + -2v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '2v' to each side of the equation. -28 + 2v = -36 + -2v + 2v Combine like terms: -2v + 2v = 0 -28 + 2v = -36 + 0 -28 + 2v = -36 Add '28' to each side of the equation. -28 + 28 + 2v = -36 + 28 Combine like terms: -28 + 28 = 0 0 + 2v = -36 + 28 2v = -36 + 28 Combine like terms: -36 + 28 = -8 2v = -8 Divide each side by '2'. v = -4 Simplifying v = -4
| .67v+.1666=.7777v+-.83333 | | -9=0.45n | | -19m+12=-14m+-8 | | 2(x-5)2+27=x | | 2(x-5)2+9=x | | n-5n-(-n)= | | 12y=64+4y | | 10r-11=8r+19 | | 90=50/x | | x^2+4x-2=-2 | | .60k+.70=.73k+-.40 | | 2(x-5)2+4=x | | .90=50/x | | Y=0.33x+1 | | 4y-18=2y+14 | | (x+5)+22=90 | | 8y-6=6y+20 | | 2x+8=4x+-2 | | 3x(x-4)=(x-10)(x-2) | | 6a^2b+7ab-3b= | | 11t-14=4t+7 | | -0.5x^2+4.5x=0 | | 13t-13=8t+2 | | -12+0.1= | | 27.98(28)=-1.891*28+96.053 | | 14t-6=9t+19 | | -2(a+3)-a=10 | | 10p+120=x | | X+50+30x+2x+10=180 | | 1.2x+37=2.2x+-4.5 | | f(f+6)=23 | | 13s-13=3s+17 |